Cerebral Small Vessel Disease Burden Is Associated With Accelerated Poststroke Cognitive Decline: A 1-Year Follow-Up Study. (November 2019) - Liang, Yan; Chen, Yang-Kun; Liu, Yong-Lin; Mok, Vincent C. T.; Ungvari, Gabor S.; Chu, Winnie C. W.; Seo, Sang Won; Tang, Wai-Kwong
Objective: This study investigated the association between small vessel disease (SVD) burden, a combination of multiple SVD markers and cognitive dysfunction after stroke. Methods: The study sample comprised 451 patients with first-ever acute ischemic stroke. Cognitive functions were assessed with the Mini-Mental State Examination (MMSE) at 3, 9, and 15 months after the index stroke. Cognitive impairment was defined as an MMSE score of ≤26. A total SVD score, indicating SVD burden, was constructed by summing the scores of the 4 SVD markers (white matter hyperintensities [WMHs], lacunes, cerebral microbleeds, and perivascular spaces) ascertained by magnetic resonance imaging (range: 0-4). The association between SVD burden and cognitive dysfunction was assessed with linear mixed models or generalized estimating equation models, as appropriate. Results: The majority of patients had mild-to-moderate stroke and at least one identifiable SVD marker. Cognitive impairment was found in about one-third of patients. After adjusting for confounding factors, the SVD burden was associated with MMSE scores (β = −0.37, P = .003) and cognitive impairment (odds ratio [OR] = 1.20, 95% confidence interval [CI] = 1.02-1.42). SVD burden was specifically associated with the performance of MMSE subscores including orientation to place and time, calculation, and word recall. Of the SVD markers, WMHs was the most robust predictor of decrease in MMSE scores (β = −0.25, P = .01) and cognitive impairment (OR = 1.14, 95% CI = 1.01-1.29). Conclusion: Cerebral SVD burden is associated with decreased MMSE scores, suggesting cognitive dysfunction during the first year after mild-to-moderate acute ischemic stroke.